A lyapunov‐based adaptive voltage controller for a grid connected PV system. Issue 4 (16th June 2021) - Bhunia, Malay; Subudhi, Bidyadhar; Ray, Pravat Kumar
Abstract: A new Lyapunov‐based adaptive controller (LBAC) for a single stage three‐phase grid‐connected PV system (GCPVS) is proposed here. The uncertainties in solar irradiation affects the performance of the GCPVS. Further, ageing in the DC‐link capacitor affects the PV voltage tracking. To achieve an improved performance of the GCPVS under both high and low irradiation, and under an aged DC‐link capacitor, a new LBAC scheme has been proposed to control the PV voltage. In this LBAC, the gains of the controller are adapted online by a Lyapunov‐based adaptation mechanism to provide the nominal tracking response of PV voltage. Further, a maximum power point tracking algorithm and grid current controllers are designed to transfer the maximum PV power to the grid, ensuring good power quality. As a result, improved performances of the GCPVS are achieved in terms of low PV voltage ripple, enhancement of delivered grid energy, and low grid current total harmonics distortion (THDs). Computer simulation studies are carried out in MATLAB/Simulink environment to verify the effectiveness of the proposed LBAC. Further, experiments are performed in a 2.5 kW GCPVS prototype for real time implementation of the proposed controller. The total harmonics distortion (THD) of grid currents is found to be within IEEE‐1547 standards.